A comprehensive diagnostic approach using galactomannan, targeted β‐d‐glucan, baseline computerized tomography and biopsy yields a significant burden of invasive fungal disease in at risk haematology patients. (1st September 2014) - Ceesay, M. Mansour; Desai, Sujal R.; Berry, Lisa; Cleverley, Joanne; Kibbler, Christopher C.; Pomplun, Sabine; Nicholson, Andrew G.; Douiri, Abdel; Wade, Jim; Smith, Melvyn; Mufti, Ghulam J.; Pagliuca, Antonio
Summary Invasive fungal disease (IFD) is difficult to diagnose. We investigated the incidence of IFD and risk factors using the revised European Organization for Research and Treatment of Cancer (EORTC) and the Mycoses Study Group (MSG) definitions. Patients (N = 203) undergoing intensive therapy with expected neutropenia ≥10 d were recruited prospectively and followed for a median (range) of 556 (12–730) d. Baseline chest computerized tomography (CT) was performed pre‐therapy. Twice‐weekly surveillance with galactomannan (GM) was combined with targeted β‐d‐glucan (BDG) testing on patients with possible IFD or who were GM‐positive. Tissue diagnosis was obtained whenever possible. The cumulative incidence of proven/probable IFD among the 202 evaluable cases after 2 years follow‐up was 21%, including 14 proven and 30 probable IFDs. Using either GM or BDG as the sole biomarker (plus host and clinical evidence) the apparent overall incidence of proven/probable IFD was 11% and 16%, respectively. Combined GM/BDG detected all biopsy‐proven mould IFD. Baseline CT abnormalities were found in 76/202 (38%) patients. Baseline CT abnormalities and Karnofsky score <90, monocytopenia >10 d and bacteraemia were independent risk factors associated with greater than twofold increased IFD risk. This combined diagnostic approach identified a high incidence of IFD and important risk factors in this cohort.